2009
DOI: 10.4102/sajhrm.v7i1.179
|View full text |Cite
|
Sign up to set email alerts
|

The influence of performance appraisal on the psychological contract of the inpatriate manager

Abstract: This article explores the extent, nature and limitations of performance appraisals, and the subsequent influence that these issues may have on the psychological contract of inpatriate managers in a sector of the health care industry in Australia. Eighteen in-depth interviews using a grounded theory methodology revealed that the process was significantly influenced by multinational organisations’ emphasis on the bottom line and the inpatriate manager’s relationship with his/her supervisor. Furthermore, the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…However, he/she may also feel superior in some respects. For example, many inpatriate managers have been successful host country managers (Maley, 2009). Likewise, host countries have become more advanced, economically and socially and their workers are becoming more progressively skilled and qualified (Beechler, Pucik, Stephan, & Campbell, 2005).…”
Section: Theoretical Foundation For Predicting Status On Inpatriate Amentioning
confidence: 99%
“…However, he/she may also feel superior in some respects. For example, many inpatriate managers have been successful host country managers (Maley, 2009). Likewise, host countries have become more advanced, economically and socially and their workers are becoming more progressively skilled and qualified (Beechler, Pucik, Stephan, & Campbell, 2005).…”
Section: Theoretical Foundation For Predicting Status On Inpatriate Amentioning
confidence: 99%
“…This result suggests that fairness perception aff ects psychological contract and OCB independently, rather than serving as a moderator. Future study may explore the eff ect of fairness perception based on employee reaction that is recently documented as an emerging issues in relative studies (Maley, 2009;Jawahar, 2007;Harvath & Andrews, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…One important aspect regarding how employees perceive their organizations may have been neglected, the psychological contract. Although prior evidences have indicated that performance appraisal results in a perception of violation of the employee's psychological contract with the organization (i.e., Maley, 2009), the eff ect of fairness perception of performance appraisal has not yet been intensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The inpatriate manager has customarily been a subsidiary manager or senior employee who is relocated to the MNC's HQ (Moeller et al, ). It has been projected that 92% of inpatriates have previously held roles as host‐country managers of subsidiaries (Tharenou & Harvey, ), and in their former senior executive roles, they have typically successfully managed several hundred employees and had total financial responsibility for the subsidiary—they have proven their worth in the subsidiary (Maley & Moeller, ). They have strong local knowledge and local business connections, which allow the MNC to obtain economically valuable local resources and to adapt to local environments (Reiche, ).…”
Section: The Inpatriate Managermentioning
confidence: 99%
“…Conversely, despite the importance of durable networks, inpatriates generally have fewer working and socializing experiences within the MNC (Tan & Mahoney, ) and have less of a chance to be properly integrated into the HQ environment. According to Maley (), inpatriate managers require high levels of discourse in the form of regular and appropriate feedback from their supervisors in order to build a strong commitment to their organization. Maley and Moeller () found that host‐country managers have an intense requirement to voice their opinion—perhaps this need continues when the host‐country manager relocates to HQ.…”
Section: The Inpatriate Managermentioning
confidence: 99%